2014
DOI: 10.1088/0004-637x/788/1/64
|View full text |Cite
|
Sign up to set email alerts
|

WINDS OF LOW-METALLICITY OB-TYPE STARS:HST-COS SPECTROSCOPY IN IC 1613

Abstract: We present the first quantitative UV spectroscopic analysis of resolved OB stars in IC 1613. Because of its alleged very low metallicity ( 1/10 Z ⊙ , from H II regions), studies in this Local Group dwarf galaxy could become a significant step forward from the SMC towards the extremely metal-poor massive stars of the early Universe. We present HST-COS data covering the ∼1150-1800Å wavelength range with resolution R∼2500. We find that the targets do exhibit wind features, and these are similar in strength to SMC… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
75
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(84 citation statements)
references
References 95 publications
9
75
0
Order By: Relevance
“…In units of the Newtonian gravity, this correction factor is (1 − Γ e ), where Γ e is the Eddington factor for Thomson scattering. This treatment of terminal velocity ignores the large scatter that exists around the ∞ versus esc relation (see discussions in Kudritzki & Puls 2000;Garcia et al 2014 4541,4686,Hδ,Hγ,Hβ,and Hα. For a subset of stars (those with the earliest spectral subtypes, and mid-and late-O supergiants), our set of H and He diagnostic lines was not sufficient to accurately constrain their parameters.…”
Section: Atmosphere Fittingmentioning
confidence: 99%
“…In units of the Newtonian gravity, this correction factor is (1 − Γ e ), where Γ e is the Eddington factor for Thomson scattering. This treatment of terminal velocity ignores the large scatter that exists around the ∞ versus esc relation (see discussions in Kudritzki & Puls 2000;Garcia et al 2014 4541,4686,Hδ,Hγ,Hβ,and Hα. For a subset of stars (those with the earliest spectral subtypes, and mid-and late-O supergiants), our set of H and He diagnostic lines was not sufficient to accurately constrain their parameters.…”
Section: Atmosphere Fittingmentioning
confidence: 99%
“…Moreover, the independent works of Garcia et al (2014) and Hosek et al (2014) have found evidence that the Fe abundance in IC 1613 and NGC 3109 may be higher than the 1/7Fe value inferred from oxygen. Since Fe is the main driver of the massloss, this mismatch could explain the strong-wind problem.…”
Section: Introductionmentioning
confidence: 97%
“…Studies like those performed by Kudritzki (2002), Evans & Howarth (2003), Mokiem et al (2004Mokiem et al ( , 2006, Massey et al (2005), Trundle et al (2007), Tramper et al (2011Tramper et al ( , 2014, Garcia & Herrero (2013;hereafter GH13), and Garcia et al (2014) analyzed the dependence of effective temperature, wind properties, or ionizing flux on metallicity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bi-stability jump (Pauldrach & Puls 1990) is observed as a drop in the ratio between the terminal and escape velocities ( ∞ / esc ) of B-type supergiants (Bsgs) by a factor 2, when the effective temperature (T eff ) falls below ∼21 000 K (Lamers et al 1995;Crowther et al 2006;Markova & Puls 2008;Garcia et al 2014). Vink et al (1999) showed that this was the result of the recombination of the dominant wind driver from Fe iv to Fe iii.…”
Section: Introductionmentioning
confidence: 99%